Electrochemical Immunoassay of Melanoma Biomarker CPEB4 Based on Cobalt Porphyrin Functionalized Graphene Oxide. Issue 2 (1st February 2022) - Ye, Shan; Liu, Yanju; Zeng, Mengnan; Feng, Weisheng; Yang, Huaixia; Zheng, Xiaoke
Abstract : Rapid and early detection of cytoplasmic polyadenylate element-binding protein 4 (CPEB4) can protect against advanced malignant melanoma. Herein, we developed a sandwich electrochemical immunosensor based on GO-CoPP as a signal amplifier for the highly sensitive quantitative detection of the melanoma biomarker CPEB4. The sensor used gold nanoparticles (AuNPs) as a substrate enhancer and graphene oxide (GO) polymer modified with cobalt protoporphyrin (CoPP) as a signal carrier (GO-CoPP). The AuNPs were used to capture large amounts of primary antibodies and accelerated the electron transfer rate of the substrate, while GO-CoPP can be used to provide large amounts of the signal unit CoPP and secondary antibodies. These features of the composites conferred high sensitivity and the current response of the proposed immunosensor to CPEB4. Under optimal conditions, the developed immunosensor performed well over a wide linear range of 0.1 pg ml −1 to 10 ng ml −1 with a detection limit of 0.074 pg ml −1 (S/N = 3). In summary, the sensor showed promise for a wide range of applications in the quantitative detection of other tumor markers, with good reproducibility, high selectivity, and simple and sensitive operation.